Analysis and measurement of the non-linear refractive index of SiOxNy using pedestal waveguides - Sierra, Julian H.; Carvalho, Daniel O. [UNESP]; Samad, Ricardo E.; Rangel, Ricardo C.; Alayo, Marco; IEEE (Ieee, 2019)
In this work, the non-linear refractive index (n(2)) of silicon oxynitride (SiOxNy) is determined, obtaining a value for this material of n(2) = 2.11x10(-19) m(2)/W. The results demonstrate that this material has interesting properties for the development of non-linear optical devices. The paper presents in detail the waveguide fabrication process using the pedestal technique, which allows using different materials since it does not require etching to define the sidewalls of the waveguides. We show the results of the measurement of the n(2) employing the non-linear optical phenomena of Self-Phase Modulation (SPM).
Keywords: optical devices; non-linear photonics; silicon oxynitride; self-phase modulation; non-linear refractive index; integrated photonics; microelectronics